Relationship between triglyceride-glucose index and gallstones risk: a population-based study - Liao, Quanhui; Chen, Yongtai; Peng, Quanshui; Li, Chunying (Frontiers in Endocrinology, 2024)
Background: Globally, gallstones represented a prevalent condition of the digestive system, heavily affected by metabolic dysfunctions such as obesity, dyslipidemia, insulin resistance, and diabetes. The triglyceride-glucose (TyG) index served as an accessible novel indicator for evaluating insulin resistance, offering a precise reflection of metabolic conditions. However, no studies have yet explored their relationship. The link between the TyG and gallstone risk was the primary purpose of this study.Methods: Utilized data from the public database, the National Health and Nutrition Examination Survey, for the years 2017-2020. The logit model was utilized to elucidate the connection between the TyG and the gallstones risk. The restricted cubic spline (RCS) analysis served to verify any non-linear relationships existing between them.Sensitivity analyses, encompassing both stratified and interaction analyses, were conducted to identify populations of particular interest and assess potential interactions between covariates and the TyG index.Results: A total of 4544 individuals were included. The risk of gallstones in high group was 1.6 times that of the low group. The potential cut-off value for the TyG index was 6.19. Above this threshold, there was a 40% heightened risk of gallstones with each one-unit increment in the TyG. The RCS analysis revealed the absence of a non-linear association between them. The populations warranting particular focus included those over 60 years, non-White people, individuals with a body mass index ≥25, smokers, drinkers, those with hypertension, and diabetes. Apart from smoking history, alcohol consumption, and history of diabetes, there were no interactions between other variables and the TyG index.The current study represented the inaugural investigation into the link between TyG index and the risk of gallstones. A positive correlation existed between them, signifying that an increase in TyG paralleled an elevated risk of gallstones. No non-linear relationship has been found between them. Besides, a 40% increase in gallstone risk accompanied each unit rise in TyG. Considering the convenience and accessibility of TyG in clinical settings, it has a promising potential for clinical application.